Women’s and men’s experiences with participative decision-making at workplace and organizational levels - Plückelmann, Clara; Gustafsson Sendén, Marie; Bernhard-Oettel, Claudia; Leineweber, Constanze; Sczesny, Sabine (Frontiers in Psychology, 2024)
The concept of participative decision-making (PDM) has been well established as a positive organizational factor, and has recently gained attention as a measure of gender inclusivity in the workplace. However, findings regarding gender differences in the experiences of PDM are inconclusive. This study hypothesized that women perceive themselves as less influential than men at the organizational level rather than at the workplace level. Furthermore, the study explored whether these assumed gender differences depend on the gender typicality of occupational positions and professions. We expected gender differences to be more pronounced for leadership positions and male-typed professions (e.g., engineer) compared to non-male-typed occupational positions and professions (e.g., non-leadership, nurse). Methods: Data on experiences with participative decision-making at the workplace and organizational levels were drawn from a large representative Swedish survey (N = 10,500; 60% women). Results: Results showed that women experienced being less influential than men at the organizational level, but the experiences of both genders did not differ at the workplace level. The gender difference at the organizational level was not related to the gender typicality of position and profession. Discussion: Results of this study reveal that women experience less PDM than men at the organizational level but not at the workplace level, indicating that the inclusion of both men and women in strategic, large-scale decisions is imperative when evaluating gender equality at work.